“SUKLIS” METODE INDIVIDU SEBAGAI UPAYA PENINGKATAN KINERJA GURU-GURU SD NEGERI 2 CAKRANEGARA - JOHANI JOHANI (Universitas Mahasaraswati Mataram, 2018)
This research is a School Action Research (PTS) with the aim to: improve the performance of teachers through activities